High-flame-retardant high-foaming-ratio cross-linked polyolefin foaming material and preparation method thereof
By using expandable graphite and environmentally friendly flame retardant in polyolefin foaming materials, combined with an appropriate amount of foaming agent and inorganic filler, the problem of low flame retardant performance of polyolefin foaming materials is solved, and high flame retardant and high foaming are achieved Multiply and low cost effects.
Patent Information
- Application Number
- CN202411567032.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The application of existing polyolefin foaming materials in the fields of construction, electrical appliances, pipeline equipment insulation is limited by their low flame retardant properties, and the addition of flame retardant and inorganic fillers will affect the foaming effect.
High-efficiency environmentally friendly flame retardants such as expandable graphite and environmentally friendly flame retardants, combined with appropriate amounts of foaming agent and inorganic fillers, and high flame retardant and foaming cross-linking is prepared through refining, extrusion, calendering and foaming processes. Polyolefin foaming material.
The combination of high flame retardant performance and high foaming ratio is achieved, which reduces production costs and simplifies the preparation process, avoiding the steps of preparing masterbatches in advance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material and a preparation method thereof. Background Art
[0002] Chemically cross-linked polyolefin foam materials have excellent waterproof, moisture-proof, heat-insulating, sound-insulating, and earthquake-resistant properties, as well as the characteristics of being lightweight, soft, and not easily deformed. They can be cut into various shapes and sizes as needed and are widely used in the fields of home, outdoor leisure, sports stadiums, construction, and thermal insulation. However, due to the poor fire resistance of polyolefin materials, their application in the fields of construction, electrical appliances, and thermal insulation of pipeline equipment is limited.
[0003] At present, polyolefin materials prepared by adding flame retardants have been widely used. However, in order to obtain highly flame-retardant products, it is often necessary to add a large amount of flame retardants and inorganic fillers to the polyolefin materials. These fillers usually have an adverse effect on the preparation of polyolefin foam materials. In order to obtain polyolefin foam materials with good foaming effects, it is necessary to reduce the content of flame retardants and inorganic fillers, which will inevitably reduce the flame retardant properties of the foamed materials. Authorization announcement number CN102020801B discloses a halogen-free flame-retardant polyethylene foam plastic and a preparation method. The BDPIE-type PN flame retardant used in this application is relatively expensive, and various masterbatches need to be prepared in advance before the preparation of the foamed material, and the process is relatively complicated. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the above-mentioned technology and provide a highly flame-retardant and high-foaming ratio cross-linked polyolefin foam material and a preparation method thereof, which is environmentally friendly, has good flame retardant effect, high foaming ratio and low production cost.
[0005] To this end, the present invention provides a highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material, characterized in that the foam material is composed of the following parts by mass: 50-70 parts of polyolefin, 1-20 parts of foaming agent, 0-2 parts of foaming agent activator, 0.1-1 parts of cross-linking agent, 0-1 parts of cross-linking promoter, 5-25 parts of environmentally friendly flame retardant, 0-3 parts of lubricant, and 5-20 parts of inorganic filler. The raw materials in the above parts by mass are made by mixing, extruding, calendering, foaming, trimming, and winding.
[0006] Preferably, the polyolefin is one or more of polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer, and ethylene-acrylate copolymer.
[0007] Preferably, the foaming agent is one or more of azodicarbonamide, 4,4′-oxybisbenzenesulfonylhydrazide, toluenesulfonyl semicarbazide, triphosphorus-based triazine, 5-phenyltetrazolyl, azobisisobutyronitrile, barium azodicarboxylate, azodicarboxylic acid esters, dinitrosopentamethylenetetramine, N,N′-dinitrosopentamethylenetetramine, N,N′-dimethyl-N,N-dinitrosoterephthalamide and trinitrosotrimethylenetriamine; the activator of the foaming agent is one or more of zinc oxide, aluminum oxide, zirconium oxide, tin oxide, cadmium oxide, zinc carbonate, zinc acetate, calcium stearate and zinc stearate.
[0008] Preferably, the crosslinking agent is one or more of dibenzoyl peroxide, diisopropyl di-tert-butyl peroxide, diisopropyl peroxide, diacetyl peroxide, tert-butyl peroxypivalate, and diphenyl peroxydicarbonate.
[0009] Preferably, the crosslinking accelerator is one or more of triallyl cyanurate, triallyl isocyanurate, trimethylolpropane trimethacrylate and trimethylolpropane triacrylate.
[0010] Preferably, the environmentally friendly flame retardant is one or more of ammonium polyphosphate, alkyl aluminum phosphinate, diethyl aluminum phosphinate, red phosphorus, phosphate ester, phosphite ester, magnesium hydroxide, melamine, melamine cyanurate, melamine-pyrophosphate, and sulfonate.
[0011] Preferably, the lubricant is one or more of ethylene bisstearamide, erucamide, paraffin, silicone oil, stearic acid, calcium stearate, and magnesium stearate.
[0012] Preferably, the inorganic filler is one or more of expandable graphite, talc, light calcium carbonate, heavy calcium carbonate, mica powder, silicon dioxide, titanium dioxide, barium sulfate, montmorillonite, and kaolin, and has a particle size of 0.01-20 μm, preferably 1-15 μm.
[0013] The present invention provides a method for preparing the highly flame-retardant and highly foaming ratio cross-linked polyolefin foam material, comprising the following steps:
[0014] S1. Mix polyolefin, foaming agent, foaming agent activator, crosslinking agent, crosslinking accelerator, environmentally friendly flame retardant, lubricant and inorganic filler in an internal mixer at 100-125° C. for 15-25 min and a rotor speed of 20-40 r / min to form a mixture 1;
[0015] S2, adding the mixture into a single screw extruder equipped with a T-shaped die head for melting and extrusion to form a sheet, the extruder temperature is 100-130°C, and the screw speed is 10-30r / min;
[0016] S3, calendering the extruded sheet through a calender, and sending it into a horizontal foaming furnace for foaming to produce a closed-cell chemically cross-linked polyolefin foam material, the temperature of the foaming furnace being 190-250°C;
[0017] S4, cutting the edges of the closed-cell chemically cross-linked polyolefin foam material and rolling it up.
[0018] Preferably, the foaming ratio of the closed-cell chemically cross-linked polyolefin foam material is 20-35 times, preferably 20-30 times.
[0019] The beneficial effects of the present invention are as follows: the present invention provides a highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material and a preparation method thereof, which have the following beneficial effects.
[0020] ⑴ Use expandable graphite and other inorganic fillers together with efficient and environmentally friendly flame retardants suitable for chemical cross-linked polyolefin foaming process, and adjust the appropriate amount of foaming agent to prepare chemical cross-linked polyolefin foaming materials with high flame retardancy and high foaming ratio. There is no need to prepare various masterbatches in advance, and the preparation process is simple. Since expandable graphite has a lamellar structure, soft texture and certain elasticity, it is conducive to the foaming of polyolefin materials, and can effectively overcome the adverse effects of large-scale use of other flame retardants or fillers on polyolefin foaming;
[0021] (2) The product has fine and uniform pores, a smooth surface, a high foaming ratio and a simple process, which fully exerts the flame retardant effect of expandable graphite and environmentally friendly flame retardants, reduces the use of other environmentally friendly flame retardants, and effectively reduces production costs. DETAILED DESCRIPTION
[0022] The present invention is further described below in conjunction with specific examples to help understand the content of the present invention. The methods used in the present invention are all conventional methods unless otherwise specified; the raw materials and devices used are all conventional commercially available products unless otherwise specified.
[0023] Embodiment 1:
[0024] A highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material is prepared from polyolefin, a foaming agent, an activator of the foaming agent, a cross-linking agent, a cross-linking promoter, an environmentally friendly flame retardant, an inorganic filler and a lubricant through mixing, extruding, calendering, foaming, trimming and rolling.
[0025] The method for preparing the highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material comprises the following steps:
[0026] (1) kneading 25 kg of low-density polyethylene, 2.5 kg of ethylene-vinyl acetate copolymer, 7.5 kg of azodicarbonamide, 0.3 kg of dicumyl peroxide, 0.2 kg of triallyl cyanurate, 1 kg of silicon dioxide, 8 kg of red phosphorus, 5 kg of expandable graphite, 0.25 kg of calcium stearate, and 0.25 kg of zinc oxide in an internal mixer at 115° C. for 20 min at a rotor speed of 40 r / min to form a mixture 1;
[0027] (2) adding the mixture into a single screw extruder equipped with a T-shaped die head, melting and extruding to form a sheet, the extruder temperature is 125° C., and the screw speed is 15 r / min;
[0028] (3) The extruded sheet is calendered by a calender and sent to a horizontal foaming furnace for foaming to produce a closed-cell chemically cross-linked polyolefin foam material, and the foaming furnace temperature is 235° C.;
[0029] (4) Cut the edges of the closed-cell chemically cross-linked polyolefin foam material and then roll it up.
[0030] The closed-cell chemically cross-linked polyolefin foam material has a foaming ratio of 20-35 times, preferably 20-30 times.
[0031] Embodiment 2:
[0032] A highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material is prepared from polyolefin, a foaming agent, an activator of the foaming agent, a cross-linking agent, a cross-linking promoter, an environmentally friendly flame retardant, an inorganic filler and a lubricant through mixing, extruding, calendering, foaming, trimming and rolling.
[0033] The method for preparing the highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material comprises the following steps:
[0034] (1) kneading 25 kg of low-density polyethylene, 2.5 kg of ethylene-vinyl acetate copolymer, 7.5 kg of azodicarbonamide, 0.3 kg of dicumyl peroxide, 0.2 kg of triallyl cyanurate, 1 kg of silicon dioxide, 8 kg of diethylaluminum hypophosphite, 5 kg of expandable graphite, 0.25 kg of calcium stearate, and 0.25 kg of zinc oxide in an internal mixer at 115° C. for 20 min at a rotor speed of 40 r / min to form a mixture 1;
[0035] (2) adding the mixture into a single screw extruder equipped with a T-shaped die head, melting and extruding to form a sheet, the extruder temperature is 120° C., and the screw speed is 15 r / min;
[0036] (3) The extruded sheet is calendered by a calender and sent to a horizontal foaming furnace for foaming to produce a closed-cell chemically cross-linked polyolefin foam material, and the foaming furnace temperature is 235° C.;
[0037] (4) Cut the edges of the closed-cell chemically cross-linked polyolefin foam material and then roll it up.
[0038] Embodiment 3:
[0039] A highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material is prepared from polyolefin, a foaming agent, an activator of the foaming agent, a cross-linking agent, a cross-linking promoter, an environmentally friendly flame retardant, an inorganic filler and a lubricant through mixing, extruding, calendering, foaming, trimming and rolling.
[0040] The method for preparing the highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material comprises the following steps:
[0041] (1) kneading 23 kg of low-density polyethylene, 2.5 kg of ethylene-vinyl acetate copolymer, 7.5 kg of azodicarbonamide, 0.3 kg of dicumyl peroxide, 0.2 kg of triallyl cyanurate, 1 kg of silicon dioxide, 10 kg of ammonium polyphosphate, 5 kg of expandable graphite, 0.25 kg of calcium stearate, and 0.25 kg of zinc oxide in an internal mixer at 115° C. for 20 min at a rotor speed of 40 r / min to form a mixture 1;
[0042] (2) adding the mixture into a single screw extruder equipped with a T-shaped die head, melting and extruding to form a sheet, the extruder temperature is 120° C., and the screw speed is 15 r / min;
[0043] (3) The extruded sheet is calendered by a calender and sent to a horizontal foaming furnace for foaming to produce a closed-cell chemically cross-linked polyolefin foam material, and the foaming furnace temperature is 235° C.;
[0044] (4) Cut the edges of the closed-cell chemically cross-linked polyolefin foam material and then roll it up.
[0045] Embodiment 4:
[0046] A highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material is prepared from polyolefin, a foaming agent, an activator of the foaming agent, a cross-linking agent, a cross-linking promoter, an environmentally friendly flame retardant, an inorganic filler and a lubricant through mixing, extruding, calendering, foaming, trimming and rolling.
[0047] The method for preparing the highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material comprises the following steps:
[0048] (1) kneading 24 kg of low-density polyethylene, 2.5 kg of ethylene-vinyl acetate copolymer, 7.5 kg of azodicarbonamide, 0.3 kg of dicumyl peroxide, 0.2 kg of triallyl cyanurate, 1 kg of silicon dioxide, 9 kg of melamine cyanurate, 5 kg of expandable graphite, 0.25 kg of calcium stearate, and 0.25 kg of zinc oxide in an internal mixer at 115° C. for 20 min at a rotor speed of 40 r / min to form a mixture 1;
[0049] (2) adding the mixture into a single screw extruder equipped with a T-shaped die head, melting and extruding to form a sheet, the extruder temperature is 120° C., and the screw speed is 15 r / min;
[0050] (3) The extruded sheet is calendered by a calender and sent to a horizontal foaming furnace for foaming to produce a closed-cell chemically cross-linked polyolefin foam material, and the foaming furnace temperature is 235° C.;
[0051] (4) Cut the edges of the closed-cell chemically cross-linked polyolefin foam material and then roll it up.
[0052] Embodiment 5:
[0053] A highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material is prepared from polyolefin, a foaming agent, an activator of the foaming agent, a cross-linking agent, a cross-linking promoter, an environmentally friendly flame retardant, an inorganic filler and a lubricant through mixing, extruding, calendering, foaming, trimming and rolling.
[0054] The method for preparing the highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material comprises the following steps:
[0055] (1) kneading 23 kg of low-density polyethylene, 2.5 kg of ethylene-vinyl acetate copolymer, 7.5 kg of azodicarbonamide, 0.3 kg of dicumyl peroxide, 0.2 kg of triallyl cyanurate, 10 kg of phosphite, 5 kg of expandable graphite, 0.25 kg of calcium stearate, and 0.25 kg of zinc oxide in an internal mixer at 115° C. for 20 min at a rotor speed of 40 r / min to form a mixture 1;
[0056] (2) adding the mixture into a single screw extruder equipped with a T-shaped die head, melting and extruding to form a sheet, the extruder temperature is 120° C., and the screw speed is 15 r / min;
[0057] (3) The extruded sheet is calendered by a calender and sent to a horizontal foaming furnace for foaming to produce a closed-cell chemically cross-linked polyolefin foam material, and the foaming furnace temperature is 235° C.;
[0058] (4) Cut the edges of the closed-cell chemically cross-linked polyolefin foam material and then roll it up.
[0059] Test method:
[0060] Test standard for limiting oxygen index of highly flame-retardant and highly foaming ratio chemically cross-linked polyolefin foam materials:
[0061] The test was conducted using the GB / T 2406.1-2008 standard “Determination of Combustion Behavior of Plastics by Oxygen Index Method”.
[0062] The following table shows the performance test results of the highly flame-retardant and highly foaming ratio chemically cross-linked polyolefin foam materials of Examples 1-5.
[0063] performance Example 1 Example 2 Example 3 Example 4 Example 5 Limiting oxygen index (%) 28 32 31 29 28 <![CDATA[Density (kg / m 3 )]]> 41 39 40 42 43
[0064] The best embodiment of the present invention is embodiment 2. Compared with embodiments 1, 3, 4, and 5, the limiting oxygen index in embodiment 2 is the highest, indicating that it has the best flame retardant performance; and the density is the lowest, indicating that it has the highest foaming ratio.
[0065] It can be seen from the comparison between Example 1 and Example 2 that, when other variables are the same, the environmentally friendly flame retardant in Example 1 uses red phosphorus, and the extruder temperature is 125°C, and the environmentally friendly flame retardant in Example 2 uses diethyl aluminum hypophosphite, and the extruder temperature is 120°C. Compared with red phosphorus, diethyl aluminum hypophosphite does not contain halogen, produces less smoke and toxic gases when burned, and meets modern environmental protection requirements. At the same time, it has good compatibility with various polymer materials such as low-density polyethylene and ethylene-vinyl acetate copolymer, and can be evenly dispersed in the material, thereby improving the overall flame retardant properties of the material. It has a small particle size, good dispersibility, is easy to be evenly distributed in the material, and has good flame retardant properties. Using diethyl aluminum hypophosphite can obtain a good foaming effect when the extruder temperature is 120°C, while the formula using red phosphorus needs to be extruded at a higher temperature (125°C). Higher temperatures may cause the material to decompose or cross-link excessively, thereby affecting the foaming performance. Therefore, the raw materials in Example 2 can obtain a good foaming effect at a lower temperature, reduce energy consumption, and reduce production costs.
[0066] By comparing Examples 3-5 and 2, it can be seen that when the extruder temperature is 120°C and the types and mass fractions of the foaming agent and the foaming agent activator are the same, the weight of the environmentally friendly flame retardant in Example 2 is less than that of Example 3-5, but its limiting oxygen index is the highest and the flame retardant performance is the best; the types and mass fractions of the foaming agent and the foaming agent activator are the same, but its density is the lowest and the foaming ratio is the highest. The main reason is that the flame retardant mechanism of ammonium polyphosphate in Example 3, melamine cyanurate in Example 4, and phosphite in Example 5 may rely more on physical effects (such as diluting the concentration of combustible gases, forming a protective layer, etc.), while the diethyl aluminum hypophosphite in Example 2 mainly achieves flame retardancy through the gas phase mechanism. The gas phase mechanism can usually exert a flame retardant effect at a lower temperature, and has a more direct and significant impact on the combustion performance of the material. When other variables are the same, the higher density of environmentally friendly flame retardants increases the density of the foamed material, and a large amount of environmentally friendly flame retardants will limit the expansion of the bubbles. As the content of environmentally friendly flame retardants increases, the foaming ratio of the polyolefin foam material gradually decreases.
[0067] The highly flame-retardant and high-foaming ratio cross-linked polyolefin foam material and the preparation method thereof in the present invention are environmentally friendly, have good flame-retardant effects, high foaming ratios, low production costs, do not require the preparation of various masterbatches in advance, and have a simple preparation process.
[0068] However, what is described above is only a specific embodiment of the present invention and should not be used to limit the scope of implementation of the present invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the scope of protection of the present invention should still fall within the scope covered by the claims of the present invention.
Claims
1. A highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material, characterized in that: The foaming material is composed of the following parts by mass: 50-70 parts of polyolefin, 1-20 parts of foaming agent, 0-2 parts of foaming agent activator, 0.1-1 parts of cross-linking agent, 0-1 parts of cross-linking promoter, 5-25 parts of environmentally friendly flame retardant, 0-3 parts of lubricant and 5-20 parts of inorganic filler. The raw materials in the above parts by mass are made by mixing, extruding, calendering, foaming, trimming and winding.
2. The highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 1, characterized in that: The polyolefin is one or more of polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer, and ethylene-acrylate copolymer.
3. The highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 1, characterized in that: The foaming agent is one or more of azodicarbonamide, 4,4′-oxybisbenzenesulfonylhydrazide, toluenesulfonyl semicarbazide, triphosphorus-based triazine, 5-phenyltetrazolyl, azobisisobutyronitrile, barium azodicarboxylate, azodicarboxylic acid esters, dinitrosopentamethylenetetramine, N,N′-dinitrosopentamethylenetetramine, N,N′-dimethyl-N,N-dinitrosoterephthalamide and trinitrosotrimethylenetriamine; the activator of the foaming agent is one or more of zinc oxide, aluminum oxide, zirconium oxide, tin oxide, cadmium oxide, zinc carbonate, zinc acetate, calcium stearate and zinc stearate.
4. The highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 1, characterized in that: The cross-linking agent is one or more of dibenzoyl peroxide, diisopropyl di-tert-butyl peroxide, diisopropyl peroxide, diacetyl peroxide, tert-butyl peroxypivalate, and diphenyl peroxydicarbonate.
5. The highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 1, characterized in that: The crosslinking accelerator is one or more of triallyl cyanurate, triallyl isocyanurate, trimethylolpropane trimethacrylate and trimethylolpropane triacrylate.
6. The highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 1, characterized in that: The environmentally friendly flame retardant is one or more of ammonium polyphosphate, alkyl aluminum phosphinate, diethyl aluminum phosphinate, red phosphorus, phosphate ester, phosphite ester, magnesium hydroxide, melamine, melamine cyanurate, melamine-pyrophosphate, and sulfonate.
7. The highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 1, characterized in that: The lubricant is one or more of ethylene bisstearamide, erucamide, paraffin, silicone oil, stearic acid, calcium stearate, and magnesium stearate.
8. The highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 1, characterized in that: The inorganic filler is one or more of expandable graphite, talcum powder, light calcium carbonate, heavy calcium carbonate, mica powder, silicon dioxide, titanium dioxide, barium sulfate, montmorillonite and kaolin, and has a particle size of 0.01-20 μm.
9. A method for preparing a highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material, characterized in that: The following steps are involved: S1. Mix polyolefin, foaming agent, foaming agent activator, crosslinking agent, crosslinking accelerator, environmentally friendly flame retardant, lubricant and inorganic filler in an internal mixer at 100-125° C. for 15-25 min and a rotor speed of 20-40 r / min to form a mixture 1; S2, adding the mixture into a single screw extruder equipped with a T-shaped die head for melting and extrusion to form a sheet, the extruder temperature is 100-130°C, and the screw speed is 10-30r / min; S3, calendering the extruded sheet through a calender, and sending it into a horizontal foaming furnace for foaming to produce a closed-cell chemically cross-linked polyolefin foam material, the temperature of the foaming furnace being 190-250°C; S4, cutting the edges of the closed-cell chemically cross-linked polyolefin foam material and rolling it up.
10. The method for preparing a highly flame-retardant and high-foaming-ratio cross-linked polyolefin foam material according to claim 9, characterized in that: The closed-cell chemically cross-linked polyolefin foam material has a foaming ratio of 20-35 times.
Citation Information
Patent Citations
Halogen-free flame-retardant polyethylene foaming plastic and preparation method
CN102020801B